Digestive Symptoms in Older Adults: Prevalence and Associations with Institutionalization and Mortality - Turki AlAmeel; Mohammed Basheikh; Melissa K Andrew (Canadian Journal of Gastroenterology)
BACKGROUND: Digestive symptoms are common in adults. However, little is known about their prevalence in older adults and the association of digestive symptoms with institutionalization and mortality in community-dwelling older adults.